The Independence and Impartiality of Mosalaki in Resolving the La'a Sala Case in Ngada Regency, East Nusa Tenggara - Dhone, Kristina; Subyanto, Achmad Edy (Politeknik Siber Cerdika Internasional, 2025)
In Ngada Regency, East Nusa Tenggara Province, Mosalaki plays a crucial role as a customary leader in resolving disputes, including La’a Sala cases related to violations of customary marriage norms. However, the issues of Mosalaki’s independence and impartiality have often been debated, particularly when faced with social pressures and local political interests. This study aims to analyze the extent of Mosalaki’s independence and objectivity in handling La’a Sala cases, identify supporting and inhibiting factors, and evaluate the relevance of this role in the context of protecting the rights of indigenous communities. The study adopts a descriptive qualitative approach, combining legislative, conceptual, historical, and comparative perspectives. Data were collected through field observations, in-depth interviews with Mosalaki and community leaders, and document analysis. The data were analyzed using a thematic analysis approach, which involved coding, categorization, and source triangulation. The findings reveal that Mosalaki is capable of maintaining decision-making independence through customary mechanisms based on consensus, despite facing challenges such as family intervention, group pressure, and external interests. Factors such as customary legitimacy, community support, and an understanding of the cosmological values of La’a Sala serve as the main pillars of this independence. These findings underscore the importance of enhancing Mosalaki’s capacity through customary law education and formal legal protection, thereby contributing to the development of policies that bridge customary and national law, while enriching the literature on restorative justice rooted in local wisdom in Indonesia.